Physical Activity as a Predicting of Lower Body Mass Index (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The study aims to determine predicting factors main increasing physical activity on weight loss for students. The factors influence obesity is low physical activity, related lifestyle due to technology development. Physical activity for adolescents is a strategy to prevent non-communicable diseases through weight loss mechanisms. The study design is were used a cross sectional design. The sample size is 115 samples. Sampling was collected by systematic random sampling. The study research variables include physical activity variables divided into two indicators are learning activities and recreational activities. BMI variables divided weight and height. Data analysis was carried out by analyzing linear regression tests to see predictions of increased physical activity. Average of physical activity 743.21 ± 505.37, and BMI is 22.30±4.89 Learning activities had a dominant impact on BMI compared to body weight and height. Increasing activity for 209 minutes have been predicting weight loss 1 kilo in a week. Increasing physical activity for 236 minutes every day can reduce BMI by 1 point. The Learning physical activity significantly reduces body weight and BMI but does not significantly reduce body height. Physical activity for 209 minutes every day can predict weight loss of 1 kilogram in a week.